A feasibility study of the use of reactive tracers to determine outdoor daytime OH radical concentrations within the urban environment. (4th February 2014) - White, Iain R.; Martin, Damien; Petersson, K. F.; Henshaw, Stephen J.; Nickless, Graham; Lloyd‐Jones, Guy C.; Clemitshaw, Kevin C.; Shallcross, Dudley E.
Abstract Using a specifically designed chemical tracer to indirectly measure local atmospheric hydroxyl radical (OH) concentrations is a very appealing concept. Such a tracer will provide information on the amount of OH a tracer encounters, as it moves through the urban environment and provide a stringent test of models. However, to date an outdoor experiment such as this has not been conducted. This article discusses the reasons why this is so and examines the feasibility of using tracers to measure integrated urban OH levels over short (≤1 km) distances.